Evidence on fiscal consolidations and the evolution of public debt in Europe - Gianluca Cafiso; Roberto Cellini (Center for Economic Studies and ifo Institute (CESifo), 2012)
The objective of this paper is to gain insights into the relationship between deficit-reducing policies and the evolution of the debt/GDP ratio. We consider past events of fiscal consolidation in a selected group of EU countries, by using the new data set recently made available by Devries et al. (2011), and check what is the associated change of the debt/GDP ratio both from a short and medium-term perspective. Our results show that a favourable short-term response emerges in the majority of the countries considered, while the medium-term one is adverse for all. The analysis provides information to assess the convenience of deficit-reducing policies to contain or invert the evolution of the debt/GDP ratio.
Keywords: H63; E63; 330; fiscal consolidation; debt/GDP ratio; European Union; Haushaltskonsolidierung; Öffentliche Schulden; Sozialprodukt; EU-Staaten